The Use of Guided Imagery in Family of Origin Group Therapy - Paré, Timothy J.; Shannon-Brady, Dustin T. (Canadian Journal of Counselling and Psychotherapy, 1996)
This paper describes the use of guided imagery in a family of origin group. The group is designed to facilitate the process of differentiation from family. Awareness is identified as the key "ingredient" that contributes to the developmental task of differentiation. The paper outlines three stages in the process of differentiation from family; identification, integration and activation of the individual's thoughts, feelings and behaviours. The use of guided imageryis highlighted as a means for accessing the unconscious and increasing the clients' awareness of family issues and promoting self-differentiation. Specific examples of guided imagery for family of origin work and an innovative use of the genogram are provided.